Evaluation of physicochemical and tribological performances of hBN/WS2 and hBN/TiO2 hybrid nanoparticles-MJO-based oil - Ainaa Mardhiah Sabri, Ainaa Mardhiah Sabri; Norfazillah Talib, Norfazillah Talib; Amiril Sahab Abdul Sani, Amiril Sahab Abdul Sani; Kamaruddin Kamdani, Kamaruddin Kamdani (mytribos, 2023)
This work aims to investigate the physicochemical and tribological performance of modified Jatropha oil (MJO) with the addition of 0.025 wt.% of hexagonal boron nitride (hBN) + Titanium dioxide (TiO2) (MJOht) and hBN + tungsten disulphide (WS2) (MJOhw). The physicochemical properties of the samples were evaluated through kinematic viscosity and viscosity index. Four ball test was used to determine the tribological performance of the samples. All the MJO samples were compared with the benchmark oil, Synthetic Ester (SE). The result revealed that MJOht has excellent physicochemical properties in kinematic viscosity of 20.79 mm2/s at 40 °C and 6.29 mm2/s at 100 °C. MJOht also had the highest viscosity index (288). For tribological performance, MJOhw has an excellent coefficient of friction (COF) (0.0574) and lowest surface roughness (Ra) (0.11 μm)., while MJOht shows a smaller mean wear scar diameter (MWSD) (718.6 µm). Overall, MJO with hybrid additives shows excellent performance on physicochemical and tribological properties and making it a feasible choice as a green metalworking fluid.